Facial Cosmetics Exert a Greater Influence on Processing of the Mouth Relative to the Eyes: Evidence from the N170 Event-Related Potential Component - Tanaka, Hideaki (Frontiers in Psychology, 2016)
Cosmetic makeup significantly influences facial perception. Because faces consist of similar physical structures, cosmetic makeup is typically used to highlight individual features, particularly those of the eyes (i.e., eye shadow) and mouth (i.e., lipstick). Though event-related potentials have been utilized to study various aspects of facial processing, the influence of cosmetics on specific ERP components remains unclear. The present study aimed to investigate the relationship between the application of cosmetic makeup and the amplitudes of the P1 and N170 event-related potential components during facial perception tasks. Moreover, the influence of visual perception on N170 amplitude, was evaluated under three makeup conditions: Eye Shadow, Lipstick, and No Makeup. Electroencephalography was used to monitor 17 participants who were exposed to visual stimuli under each these three makeup conditions. The results of the present study subsequently demonstrated that the Lipstick condition elicited a significantly greater N170 amplitude than the No Makeup condition, while P1 amplitude was unaffected by any of the conditions. Such findings indicate that the application of cosmetic makeup alters general facial perception but exerts no influence on the perception of low-level visual features. Collectively, these results support the notion that the application of makeup induces subtle alterations in the processing of facial stimuli, with a particular effect on the processing of specific facial components (i.e., the mouth), as reflected by changes in N170 amplitude.